SUPERVISION OF FINANCIAL AUDIT ACTIVITY IN THE REPUBLIC OF MOLDOVA - REFORMS AND OPPORTUNITIES FOR MODERNIZATION - Anatolie IACHIMOVSCHI (Eastern European Journal of Regional Studies)
At present, financial auditing in the Republic of Moldova is supported by a legislative framework in line with international best practices and the EU acquis. However, the changing nature of services in the domestic audit market and the current challenges of meeting new quality management requirements are of interest for scientific research in this field. This paper aims to investigate the opportunities for modernization of the profession in the context of the attested reforms regarding the supervision of audit activity in the Republic of Moldova. The aim of the investigation is to highlight the importance of legislative reforms in order to increase the prestige and recognition of the professionalism of financial audit activities in the Republic of Moldova. In addition, this paper includes a study of professional qualifications in auditing and an analysis of the activities carried out by audit entities in recent years of monitoring the audit market by the supervisory authority. The issue of reforming the regulatory framework for the audit of financial statements in line with international good professional practice is considered. The investigation used the qualitative research method and the observation technique based on the analysis of national and international normative acts. The results indicate a good harmonization of the regulatory framework of the financial audit activity in the Republic of Moldova with the international practices in this field, which will contribute to the development of the domestic process of regulating the profession and at the same time will provide opportunities for modernization of the system of supervision of the quality of audit activity in the country.